On approach to the agreement of diverse stakeholders’ interests and goals in the governance - K. Avdeeva, Zinaida; V. Kovriga, Svetlana (International Journal of Engineering and Technology, 2018)
The paper proposes the use of a collective cognitive map when solving governance problems as an effective means of diverse stakeholdersâ€™ interests and goals agreement. For compose such a map, an original approach is proposed that combines (1) the clarification and agreement of stakeholder representations on the governance problem using a number of criteria for improving the map quality and (2) the clusterization of similar stakeholder representations.Â Â